2020
DOI: 10.1111/epi.16524
|View full text |Cite
|
Sign up to set email alerts
|

New onset acute symptomatic seizure and risk factors in coronavirus disease 2019: A retrospective multicenter study

Abstract: Our aim was to clarify the incidence and risk of acute symptomatic seizures in people with coronavirus disease 2019 . This multicenter retrospective study enrolled people with COVID-19 from January 18 to February 18, 2020 at 42 government-designated hospitals in Hubei province, the epicenter of the epidemic in China; Sichuan province; and Chongqing municipality. Data were collected from medical records by 11 neurologists using a standard case report form. A total of 304 people were enrolled, of whom 108 had a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
286
2
17

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 290 publications
(318 citation statements)
references
References 14 publications
8
286
2
17
Order By: Relevance
“…Overall, 25% of patients had symptoms considered as evidence of CNS dysfunction, including dizziness (17%), headache (13%), impaired consciousness (7.5%), acute cerebrovascular disease (3%), ataxia (0.5%), and seizures (0.5%). Confirming this low incidence of seizures, no cases of status epilepticus or new onset seizures were reported in a large cohort of over 304 hospitalized patients with COVID-19 in Hubei Province, China, 12 although there have been isolated case reports describing seizures at presentation in both adult and pediatric patients with COVID-19. 13,14 In the series by Mao and colleagues, 11 the patients were subdivided based on the severity of their pneumonia and pulmonary impairment, and among those with "severe" disease (n = 88) the incidence of CNS symptoms was higher (31%) compared to the non-severe group (21%), although the results were not statistically significant (p = 0.09).…”
Section: Neurological Complications Of Systemic Covid-19mentioning
confidence: 73%
“…Overall, 25% of patients had symptoms considered as evidence of CNS dysfunction, including dizziness (17%), headache (13%), impaired consciousness (7.5%), acute cerebrovascular disease (3%), ataxia (0.5%), and seizures (0.5%). Confirming this low incidence of seizures, no cases of status epilepticus or new onset seizures were reported in a large cohort of over 304 hospitalized patients with COVID-19 in Hubei Province, China, 12 although there have been isolated case reports describing seizures at presentation in both adult and pediatric patients with COVID-19. 13,14 In the series by Mao and colleagues, 11 the patients were subdivided based on the severity of their pneumonia and pulmonary impairment, and among those with "severe" disease (n = 88) the incidence of CNS symptoms was higher (31%) compared to the non-severe group (21%), although the results were not statistically significant (p = 0.09).…”
Section: Neurological Complications Of Systemic Covid-19mentioning
confidence: 73%
“…Lu et al studied 304 COVID-19 patients and concluded that none of these patients had acute symptomatic seizures or status epilepticus. [68] The current data are too limited to make any conclusions about the effects of COVID-19 on developing seizures.…”
Section: Discussionmentioning
confidence: 93%
“…Seizures in patients with COVID-19 might occur in consequence of direct brain infection, but only single reports of patients with seizures exist so far. Thus, current evidence does not suggest an additional risk of seizures in COVID-19 [41]. Encephalopathy, rather than encephalitis, may occur due to indirect mechanism of neuropathogenicity, such as hypoxic encephalopathy found in deceased COVID-19 patients [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, CSF and cerebral MRI analyses were not performed in the patient with encephalitis, leaving insecurity about diagnostic accuracy [33]. Neither acute symptomatic seizures, nor status epilepticus were observed in a more extensive retrospective study involving 304 COVID-19 patients [41].…”
Section: Seizuresmentioning
confidence: 99%